2023
DOI: 10.1021/acs.energyfuels.2c03561
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium of Methane Hydrate in Sediments: Experimental and Theoretical Characterization

Abstract: A series of phase equilibrium tests were performed to explore the influence of various experimental conditions, including initial water content, dry density, and salt content, on the phase equilibrium behavior of methane hydrate in fine- and coarse-grained sediments. The results indicate that the phase equilibrium condition of pore hydrate is significantly influenced by the adopted experimental conditions and the sediment types. It is shown that in equilibrium, a unique relationship (the soil hydration charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The influence of porous media on hydrate phase equilibrium has been extensively studied in the field of gas hydrates. The pore structure inside the porous media can affect the heat and mass transfer of the internal gas and liquid and, thus, affect the phase equilibrium conditions of hydrates . Early studies on porous media were mainly focused on simulating the natural gas occurrence environment under natural conditions to obtain a deeper understanding of the effect of porous media on the process of hydrate formation, and the main materials were usually focused on silica sand , and clay. , As research has progressed, it has been observed that porous media, including activated carbon, glass beads, carbon nanotubes, and nanomaterials, are commonly employed to enhance the formation of hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of porous media on hydrate phase equilibrium has been extensively studied in the field of gas hydrates. The pore structure inside the porous media can affect the heat and mass transfer of the internal gas and liquid and, thus, affect the phase equilibrium conditions of hydrates . Early studies on porous media were mainly focused on simulating the natural gas occurrence environment under natural conditions to obtain a deeper understanding of the effect of porous media on the process of hydrate formation, and the main materials were usually focused on silica sand , and clay. , As research has progressed, it has been observed that porous media, including activated carbon, glass beads, carbon nanotubes, and nanomaterials, are commonly employed to enhance the formation of hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey reveals that the substitution of a small quantity of Ni to SrFeO 3−d has been reported to yield positive outcomes in terms of chemical looping and dry reforming of methane. 17 Furthermore, the introduction of two distinct ions at the B site through doping has been found to enhance the activity even further, resulting in synergistic effects. This approach serves as a remarkable catalyst design strategy.…”
Section: Introductionmentioning
confidence: 99%